2014
DOI: 10.5120/15039-3385
|View full text |Cite
|
Sign up to set email alerts
|

A New Concept to Detect Isomorphism in Kinematic Chains using Fuzzy Similarity Index

Abstract: This paper presents a new method based on fuzzy similarity measure to investigate isomorphism among kinematic chains having same number of links and degrees of freedom (d.o.f.). Two different similarity measures which are available in the literature are used to compare the numerous distinct chains. General TermsIsomorphism detection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…When both the KCS of two kinematic chains are compared it was found that they are non-isomorphic in nature. The results obtained were coincident with Syed et al [16].…”
Section: Procedures To Identify Isomorphism Of Two Kinematic Chainssupporting
confidence: 80%
“…When both the KCS of two kinematic chains are compared it was found that they are non-isomorphic in nature. The results obtained were coincident with Syed et al [16].…”
Section: Procedures To Identify Isomorphism Of Two Kinematic Chainssupporting
confidence: 80%
“…Dargar, Hasan and Khan (2013) present some new codes for isomorphic detection and distinct inversions. Rizvi, Hasan and Khan (2014a) proposed a method based on fuzzy similarity index and an another method was also devised by Rizvi, Hasan and Khan (2014b) based on the instantaneous centres of the kinematic chains, Chiu and Yan (2015) presented an algorithm for automatic sketching of chains. Ding, Huang and Kecskeméthy (2015) present a method of enumeration of valid non-fractionated kinematic chains.…”
Section: Introductionmentioning
confidence: 99%